2020
DOI: 10.1039/c9np00062c
|View full text |Cite
|
Sign up to set email alerts
|

Natural disesquiterpenoids: an update

Abstract: This review highlights the progress on the isolation, bioactivity, biogenesis and total synthesis of dimeric sesquiterpenoids since 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 327 publications
0
57
0
Order By: Relevance
“…9−11 Phytochemical studies of A. fragrans have revealed its active constituents as sesquiterpene lactones and phenolic acids. 5,6,9,11,12 As part of an ongoing effort to explore biologically active substances from medicinal plants, 13−15 herein we report the isolation and structure elucidation of one novel sesquiterpene trimer (1) and two new guaianolide sesquiterpene dimers (2, 3) from the whole plants of A. f ragrans, together with nine known analogues (4−12) (Figure 1). The structures of the new compounds were determined by 1D/2D NMR spectroscopy and computational calculations.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…9−11 Phytochemical studies of A. fragrans have revealed its active constituents as sesquiterpene lactones and phenolic acids. 5,6,9,11,12 As part of an ongoing effort to explore biologically active substances from medicinal plants, 13−15 herein we report the isolation and structure elucidation of one novel sesquiterpene trimer (1) and two new guaianolide sesquiterpene dimers (2, 3) from the whole plants of A. f ragrans, together with nine known analogues (4−12) (Figure 1). The structures of the new compounds were determined by 1D/2D NMR spectroscopy and computational calculations.…”
mentioning
confidence: 63%
“…As one of the intriguing groups of natural products of plant origin, sesquiterpenoid oligomers are well-known for their complex structures and biological activities. Specifically, the Compositae family is a major source of diverse sesquiterpenoids and their oligomers and has become of great interest in the past decade. , Ainsliaea fragrans Champ. (Compositae), also known as “Xing Xiang Tu Er Feng”, is mainly distributed in South China with long history of medicinal use as an antibacterial and anti-inflammatory agent. Phytochemical studies of A. fragrans have revealed its active constituents as sesquiterpene lactones and phenolic acids. ,,,, As part of an ongoing effort to explore biologically active substances from medicinal plants, herein we report the isolation and structure elucidation of one novel sesquiterpene trimer ( 1 ) and two new guaianolide sesquiterpene dimers ( 2 , 3 ) from the whole plants of A. fragrans , together with nine known analogues ( 4 – 12 ) (Figure ).…”
mentioning
confidence: 64%
“…Up to now, a variety of sesquiterpenoid dimers with potential in the treatment of liver cancer [ 6‐7 ] and antiinflammatory activities have been isolated from Artemisia species. [ 8‐19 ] Guaiane‐type sesquiterpenoid dimers are the main classes of sesquiterpenoid dimers in this genus, predominantly composed of two alike or unlike monomeric sesquiterpene lactone units through different connecting model. Chemical investigations showed that 77 guaiane‐type sesquiterpenoid dimers had been identified from Artemisia plants in the last 40 years, and most of them were generated via intermolecular Diels–Alder reaction to produce an additional cyclohexene moiety.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…While the scientific community is generally aware of the rarity of the N bond in natural sequiterpenoids, and there are many reviews providing extensive coverage on sesquiterpenoids [11,12], including the naturally occurring disesquiterpenoids [1,13,14], natural products containing a nitrogen-nitrogen bond [15] or nitrogen-sulfur bond [16], neither the potentially valuable bioactivity nor the broad structural diversity of nitrogenous sesquiterpenoids has been systematically reviewed during the past ten years.…”
Section: Introductionmentioning
confidence: 99%